A poem Mawtini as Unofficial National Anthem of Palestine by Ibrahim Tuqan. The Michael Riffaterre's Semiotic Lens - Adellia Ifha Annisa; Ahmad Bachmid; Ahfa Rahman Syah (Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2023)
This research aims to reveal the meaning of Mawtini's poem, the unofficial national anthem of Palestine, by Ibrahim Tuqan. This study uses descriptive-analytical research using Michael Riffaterre's semiotic theory, which consists of indirect expressions, heuristic readings, hermeneutic readings, matrices, models, variants, and programs to express the meanings contained therein. The results of the research show that Mawtini's poetry contains jargon or phrases, namely: homeland, live a noble life or die a martyr's death, it is better to die than to be a slave to the enemy, sword, and ink as tools of war and narration, not afraid of death, and do not want to suffer. All of them are typical phrases or jargon of the struggle of the Middle East to expel Western invaders, especially Palestine. From there, it was concluded that Mawtini's poetry has a very deep meaning about the fighting spirit for the motherland, patriotism, and Palestinian nationalism, which later made it the unofficial national anthem of Palestine. The poem is intended to give hope and awaken the spirit of struggle to the Palestinian people in facing their enemies at that time, namely the Jews and the British in 1934 regarding the policy of unrestricted Jewish immigration and buying land to establish a